Acupuncture Modulation Effect on Pain Processing Patterns in Patients With Migraine Without Aura - Tian, Zilei; Guo, Yaoguang; Yin, Tao; Xiao, Qingqing; Ha, Guodong; Chen, Jiyao; Wang, Shuo; Lan, Lei; Zeng, Fang (Frontiers in Neuroscience, 2021)
Introduction: In this retrospective study, resting-state functional connectivity (FC) in patients with migraine was analyzed to identify potential pathological pain processing patterns and compared them to healthy controls (HCs). The FC patterns in patients between pre-and post-acupuncture sessions were also analyzed to determine how acupuncture affects neurological activity and pain perception during the migraine interictal period. Methods: In total, 52 patients with migraine without aura (MwoA) and 60 HCs were recruited. Patients with migraine were given acupuncture treatment sessions for four weeks. As a primary observation, functional magnetic resonance images (fMRI) were obtained at the beginning and end of the sessions. HCs received no treatment and underwent one fMRI scan after enrollment. After the fMRI data were preprocessed, a region of interest (ROI)-to-ROI analysis was performed with predefined ROIs related to pain processing regions. Results: The first analysis showed significantly different FCs between patients with MwoA and HCs (false discovery rate corrected p-value (p-FDR) < 0.05). The FCs were found to be mainly between the cingulate gyrus (CG) and the insular gyrus, the CG and the inferior parietal lobule (IPL), the CG and the superior frontal gyrus, and the middle frontal gyrus and the IPL. The second analysis indicated that acupuncture treatment partly restored the different FCs found in the first analysis (p-FDR < 0.05). Furthermore, subgroup analysis found different brain activity patterns in headache-intensity restored condition and headache-frequency restored condition. Lastly, the correlation analysis suggested a potential correlation between FCs and clinical symptoms (p < 0.05). Conclusion: This study suggests that pain processing is abnormal in migraine, with significantly abnormal FCs in the frontal, parietal, and limbic regions. This finding could be a typical pathological feature of migraine. Acupuncture has been identified to relieve headache symptoms in two ways: it restores the pain processing function and regulates pain perception.